2020
DOI: 10.1111/sms.13803
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training‐induced visceral fat loss in obese women: The role of training intensity and modality

Abstract: Visceral fat loss in response to four‐cycle ergometer training regimens with explicit differences in exercise intensity and modality was compared. Fifty‐nine obese young women (body fat percentage ≥ 30%) were randomized to a 12‐week intervention consisting of either all‐out sprint interval training (SITall‐out, n = 11); supramaximal SIT (SIT120, 120% trueV˙O2peak, n = 12); high‐intensity interval training (HIIT90, 90% trueV˙O2peak, n = 12), moderate‐intensity continuous training (MICT, 60% trueV˙O2peak, n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 36 publications
(45 reference statements)
6
83
0
Order By: Relevance
“…Since visceral fat accumulation is a risk factor for a number of metabolic diseases, researchers have also observed the effectiveness of HIIT and MICT in reducing visceral fat in human trials. Some human studies found that HIIT reduced visceral fat similarly to MICT (Zhang et al, 2017;Tong et al, 2018), while others showed that HIIT can reduce more visceral fat (Maillard et al, 2016;Zhang et al, 2020). Animal studies have shown similar results.…”
Section: Hiit Has Similar Body Mass Controlling Effects and Better VImentioning
confidence: 90%
See 1 more Smart Citation
“…Since visceral fat accumulation is a risk factor for a number of metabolic diseases, researchers have also observed the effectiveness of HIIT and MICT in reducing visceral fat in human trials. Some human studies found that HIIT reduced visceral fat similarly to MICT (Zhang et al, 2017;Tong et al, 2018), while others showed that HIIT can reduce more visceral fat (Maillard et al, 2016;Zhang et al, 2020). Animal studies have shown similar results.…”
Section: Hiit Has Similar Body Mass Controlling Effects and Better VImentioning
confidence: 90%
“…The study design was shown in Figure 1. Since it is wellknown that the distribution of α and β 3 ARs, which receive catecholamine lipolysis signal, is not exactly same between sexes (Zouhal et al, 2013), and most of our previous HIIT human studies involved young women (Zhang et al, 2017(Zhang et al, , 2020, for maintaining research continuity, female C57Bl/6 mice (4 weeks old, Vital River Laboratories) were selected as animal models. Mice were housed, one per cage, under controlled temperature conditions (20-24°C) with a 12 h light/ dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“… Studies were conducted in women who were classified as healthy [ 10 , 46 , 47 , 49 , 52 , 54 , 65 , 69 72 , 75 , 79 , 161 ], with overweight/obesity [ 44 , 50 , 51 , 53 , 55 , 60 63 , 66 , 67 , 73 , 76 , 100 , 110 , 121 , 138 , 162 , 164 , 167 , 168 ] and/or type 2 diabetes [ 100 , 162 ]. For transparency, the same cohort of women was examined in the following pairs of references: [ 50 , 121 ] and [ 73 , 138 ].…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“… 1 Such specific training regimens have been demonstrated effective to induce energetic adaptation and fat loss in both healthy and obese people, and are generally considered as time-efficient non-pharmacological strategies for promoting cardiovascular and metabolic health. 2 , 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%